R1 retrotransposons in the nucleolar organizers of Drosophila melanogaster are transcribed by RNA polymerase I upon heat shock. Issue 5 (20th October 2018) - Raje, Himanshu S.; Lieux, Molly E.; DiMario, Patrick J.
ABSTRACT: The ribosomal RNA genes ( rDNA ) of Drosophila melanogaster reside within centromere-proximal nucleolar organizers on both the X and Y chromosomes. Each locus contains between 200–300 tandem repeat rDNA units that encode 18S, 5.8S, 2S, and 28S ribosomal RNAs (rRNAs) necessary for ribosome biogenesis. In arthropods like Drosophila, about 60% of the rDNA genes have R1 and/or R2 retrotransposons inserted at specific sites within their 28S regions; these units likely fail to produce functional 28S rRNA. We showed earlier that R2 expression increases upon nucleolar stress caused by the loss of the ribosome assembly factor, Nucleolar Phosphoprotein of 140 kDa (Nopp140). Here we show that R1 expression is selectively induced by heat shock. Actinomycin D, but not α-amanitin, blocked R1 expression in S2 cells upon heat shock, indicating that R1 elements are transcribed by Pol I. A series of RT-PCRs established read-through transcription by Pol I from the 28S gene region into R1 . Sequencing the RT-PCR products confirmed the 28S-R1 RNA junction and the expression of R1 elements within nucleolar rDNA rather than R1 elements known to reside in centromeric heterochromatin. Using a genome-wide precision run-on sequencing (PRO-seq) data set available at NCBI-GEO, we show that Pol I activity on R1 elements is negligible under normal non-heat shock conditions but increases upon heat shock. We propose that prior to heat shock Pol I pauses within the 5ʹ end of R1 where we find a consensus "pause button", and that heat shock releases Pol I for read-through transcription farther into R1 .